The Influence of the Human Resource Information System ( HRIS), Organizational Culture, Financial Incentives, and Flexible Working Space (FWS) On Employee Performance (Survey of PT Cloud Hosting Indonesia employees) - Siti Aulia Saidah; Dicky Jhoansyah; Resa Nurmala (Journal of Research in Social Science and Humanities, 2024)
This research is a study to examine the application of Human Resource Information System (HRIS), Organizational Culture, Financial Incentives and Flexible Working Space (FWS) on employees of PT. Cloud Hosting Indonesia. Specifically, the purpose of conducting research at PT Cloud Hosting Indonesia is to find out management practices in applying the concepts of HRIS, Organizational Culture, Financial Incentives and FWS along with their influence on Employee Performance, especially for employees of PT Cloud Hosting Indonesia. The scope of this research will measure the relationship between research variables both dependent variables and independent variables using quantitative methods, namely multiple linear regression methods. In this study, a research sample was taken from employees of PT Cloud Hosting Indonesia and obtained a total of 60 respondents with a sampling method using a questionnaire distributed to all employees at PT Cloud Hosting Indonesia. The results of respondents' responses from the questionnaire were processed so that the results obtained that the HRIS variables, Organizational Culture, Financial Incentives and FWS, all have a relationship between variables and a significant influence on employee performance variables at PT. Cloud Hosting Indonesia.